PENGARUH OPERASI MONETER TERHADAP INFLASI DI INDONESIA - Nurul Jannah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
This study aims to determine whether there is a significant influence between monetary operations on inflation in Indonesia. This research was also conducted to find out how monetary policy in Indonesia resolves the inflationary problems that occur. The independent variable in this study is monetary operations. Monetary operations in this study include conventional and sharia monetary operations. The dependent variable in this study is inflation. The research design used is quantitative research design using simple linear regression analysis techniques supported by the classical assumption test and statistical test with the help of SPSS v22 program. The sample of this study was monetary operations and Inflation from January 2017 to Mei 2020. The result of this research showed that the data are normally distributed, and free from multicollinearity. Then this research also shows that monetary operations have significant effect on inflation. Based on the research that has been carried out, it is known that this research is very important to be carried out as a reference for the government in solving the problem of inflation in Indonesia, considering that monetary operations are policies issued by the government in minimizing inflation.